Effect of various penetration enhancers concentrations on diclafenac sodium release from cellulose acetate phthalate polymeric film - Hanan, El-Nahas; Fakhry, Ghazy; Hanaa, El-Ghamry; Shereen, Sabry (Asian Journal of Pharmaceutics (AJP), 2014)
An investigation was conducted to evaluate the influence of different penetration enhancers in various concentrations on the release of diclofenac sodium (DFS) as a water-soluble drug from Cellulose acetate phthalate polymeric films containing 50% w/w PEG 600 as plasticizer, to choose the most appropriate enhancer and its optimum concentration to be used to achieve the maximum release and permeation of the drug. The addition of various enhancers, as isopropylmyristate (IPM; 0.2_5% w/w), oleic acid (OA; 0.2_5% w/w) and linoleic acid (LOA; 0.2_5% w/w), Tween 80 (T80;1_10% w/w) and transcutol, (TC; 1_10% w/w) enhanced the DFS release from the polymeric films. The enhancement ratio of the penetration enhancers used in the formulation of DFS were found to increase in the order of IPM>LOA>OA>T80>TC. (56.2, 54.1, 50, 48.7 and 48%, respectively). In vitro permeation studies were performed using rabbit abdominal skin as the permeating membrane. The results indicated that maximum permeation was obtained at 24hrs (0.5% IPM, 0.2% LOA, 1% OA, 0.5% T80 and 10% TC, increased skin permeation of DFS by 4.46, 4.06, 3.37, 1.65 and 1.49 time, respectively). IPM was found to be the most efficient enhancer. The results obtained from ANOVA test indicate that the difference in drug permeation rates is highly significant compared to the control formulation (P<0.05). The mechanism of drug release from the polymeric films obey Higuchi’s model.